2004
DOI: 10.1093/ansci/82.2.526
|View full text |Cite
|
Sign up to set email alerts
|

The effects of gender and slaughter weight on the growth performance, carcass traits, and meat quality characteristics of heavy pigs1

Abstract: Crossbred pigs (n = 192) from Piétrain x Large White sires mated to Landrace x Large White dams, with a mean BW of 75 +/- 1.3 kg, were used to investigate the effects of gender and slaughter weight (SW) on growth performance, carcass characteristics, and meat quality. Pens of pigs (eight pigs/pen) were assigned randomly to one of six treatments arranged in a 2 x 3 factorial design with two genders (barrows or gilts) and three SW (116, 124, or 133 kg). Each treatment was replicated four times. Over the entire t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
48
4
6

Year Published

2008
2008
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(77 citation statements)
references
References 29 publications
19
48
4
6
Order By: Relevance
“…Backfat was 7.6 mm thicker in CF than in IF but castration did not affect cooler shrink. These results are in accordance with data of Serrano et al (2008b, in press,) in IB pigs and with Latorre et al (2003aLatorre et al ( , 2004 in heavy white pigs. Cooler shrink varied from 10.3 to 11.3 g/kg, values that are lower than 20 to 30 g/kg reported by Cisneros et al (1996) and Lebret et al (2001) in white pigs.…”
Section: Carcass Traitssupporting
confidence: 93%
“…Backfat was 7.6 mm thicker in CF than in IF but castration did not affect cooler shrink. These results are in accordance with data of Serrano et al (2008b, in press,) in IB pigs and with Latorre et al (2003aLatorre et al ( , 2004 in heavy white pigs. Cooler shrink varied from 10.3 to 11.3 g/kg, values that are lower than 20 to 30 g/kg reported by Cisneros et al (1996) and Lebret et al (2001) in white pigs.…”
Section: Carcass Traitssupporting
confidence: 93%
“…The ADFI is also negatively correlated with DM content (r = −0.55). The age effect on the moisture (or DM) content and the a ⁎ value variation have also been reported in other studies (García-Macías et al, 1996;Latorre et al, 2004).…”
Section: Correlations Between Growth Performance and Meat Quality Varsupporting
confidence: 77%
“…In fact, several works have shown that the energy content of diet has a high impact on fatness in pigs (Suarez-Belloch et al, 2013) and poultry (Engel et al, 2001). In addition, Latorre et al (2004) found a negative relationship between carcass fatness and yield of main lean cuts. In this regard, in the current trial, no effect was detected on fat depth at 3rd to 4th last ribs and also pigs from all treatments had similar proportion of hams, shoulders and loins.…”
Section: Carcass Qualitymentioning
confidence: 97%
“…Besides, those pigs fed this diet had longer carcasses and wider hams. Latorre et al (2004) studied the relationship between pig slaughter weight and carcass size and observed an increase of carcass length and ham perimeter of 2 cm and 1.1 cm, respectively, per each increase of 10 kg BW. In general, shorter carcasses are commercially preferred because of their easier manipulation; however, Mediterranean consumers demand longer and thinner hams because those characteristics are currently associated to high quality hams.…”
Section: Carcass Qualitymentioning
confidence: 99%